1989
DOI: 10.1007/bf01870856
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of inositol 1,4,5-trisphosphate-sensitive (IsCaP) and-insensitive (IisCaP) nonmitochondrial Ca2+ pools in rat pancreatic acinar cells

Abstract: We have measured Ca2+ uptake and Ca2+ release in isolated permeabilized pancreatic acinar cells and in isolated membrane vesicles of endoplasmic reticulum prepared from these cells. Ca2+ uptake into cells was monitored with a Ca2+ electrode, whereas Ca2+ uptake into membrane vesicles was measured with 45Ca2+. Using inhibitors of known action, such as the H+ ATPase inhibitors NBD-Cl and NEM, the Ca2+ ATPase inhibitor vanadate as well as the second messenger inositol 1,4,5-trisphosphate (IP3) and its analog inos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

1990
1990
2000
2000

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(40 citation statements)
references
References 35 publications
1
38
1
Order By: Relevance
“…It has been proposed that rat parotid (17) and pancreatic (18) (13) have presented evidence that the plasma membrane of Neurospora possesses an ATP-driven Ca2+/H+ exchanger that is stimulated by the inwardly directed proton gradient due to the plasma membrane proton pump and advance a convincing thermodynamic argument that this interaction is important for the maintenance of low cytosolic [Ca2W] in that organism. In Dictyostelium and possibly in other cell types where there is evidence for protonophore-sensitive calcium sequestration (17)(18)(19)(20)(21)(22), if such an enzyme pumps calcium ions into an acidic compartment, then the cell could use the energy stored in the proton gradient to augment that available from ATP (13). The efficiency of calcium sequestration into acidic intracellular stores would then depend on the magnitude of the transmembrane pH gradient and should be reduced by exposure to weak bases such as ammonia.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that rat parotid (17) and pancreatic (18) (13) have presented evidence that the plasma membrane of Neurospora possesses an ATP-driven Ca2+/H+ exchanger that is stimulated by the inwardly directed proton gradient due to the plasma membrane proton pump and advance a convincing thermodynamic argument that this interaction is important for the maintenance of low cytosolic [Ca2W] in that organism. In Dictyostelium and possibly in other cell types where there is evidence for protonophore-sensitive calcium sequestration (17)(18)(19)(20)(21)(22), if such an enzyme pumps calcium ions into an acidic compartment, then the cell could use the energy stored in the proton gradient to augment that available from ATP (13). The efficiency of calcium sequestration into acidic intracellular stores would then depend on the magnitude of the transmembrane pH gradient and should be reduced by exposure to weak bases such as ammonia.…”
Section: Discussionmentioning
confidence: 99%
“…4 requires two separate Ca 2+ pools with Ca 2+ channels having different characteristics. The existence of at least two nonmitochondrial intracellular Ca 2+ pools has been proposed on the basis of studies where it can be shown that Ins (1,4,5) P3 is only able to release Ca 2+ from a minor compartment of the endoplasmic reticulum Ca 2+ pool (Biden, Wollheim & Schlegel, 1986;Thevenod et al, 1989). In the pancreatic acinar cells the two Ca 2 + pools seem to have different types of Ca 2 + uptake mechanisms.…”
Section: Two Intracellular Nonmitochondrial Ca 2+ Poolsmentioning
confidence: 98%
“…This idea is based on the data from Osipchuk et al (1990). The proposal that the Ca 2" uptake mechanisms in the Ins (1,4,5) P3-sensitive and insensitive pools are different is based on the data from Thevenod et al (1989) polypeptides with M r -400,000) with square shape (Maeda et al, 1990).…”
Section: Ins (145) P3 and Ca 2+ Activate Two Separate Types Of Ca 2mentioning
confidence: 99%
“…When cells are loaded a t high free [Ca ' 3, this component accounts for up to 35% of the sequestered Ca2 ' . It is not very likely that the thapsigargin-insensitive Ca2+ pool in LLC-PK, cells is related to the vanadateinsensitive Ca"+ pool described in pancreatic acinar cells (Thevenod et al, 1989). The vanadate-insensitive Ca" pool in the latter study was found to be InsP,-sensitive and was filled by a NEM-sensitive mechanism, which was not the case for the thapsigargin-insensitive Ca2+ pool in our study.…”
Section: Resultsmentioning
confidence: 68%